Evaluating The Efficacy Of Mindfulness-Based Therapy in Treating Anxiety Disorders - Nguyen Van Hoang; Tran Minh Quang; Pham Thanh Hien (International Journal of Health and Medicine, 2024)
This article examines the effectiveness of mindfulness-based therapy (MBT) as a treatment for anxiety disorders. Through a meta-analysis of clinical trials, the study assesses how MBT impacts anxiety levels, stress resilience, and overall mental health. The results indicate that MBT significantly reduces anxiety symptoms and improves coping mechanisms, supporting its use as a non-pharmacological treatment option for patients with anxiety.